2005
DOI: 10.1007/bf02760573
|View full text |Cite
|
Sign up to set email alerts
|

Hand-foot-and-mouth disease in calicut

Abstract: Acute and convalescent paired serum samples collected from 19 patients were examined at the NICD for IgM antibody against EV 71 by microneutralisation test in cell culture. All the paired samples tested showed significant rise in titre of antibodies, confirming the diagnosis of EV 71 infection in each of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
4
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 2 publications
1
34
4
2
Order By: Relevance
“…In India, the role of enteroviruses in causing HFMD is not very clear on account of lack of accurate diagnosis, as most of the cases reported earlier were diagnosed on the basis of clinical signs compatible with HFMD (Sarma et al, 2009). A single study conducted to investigate an outbreak of HFMD in Calicut, Kerala, identified association of EV-71 by an immunological approach (Sasidharan et al, 2005). In the present study, use of sensitive molecular methods, RT-PCR and sequencing targeted against conserved and variable regions of the EV genome revealed the presence of significant EV RNA positivity as well as multiple types in the clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, the role of enteroviruses in causing HFMD is not very clear on account of lack of accurate diagnosis, as most of the cases reported earlier were diagnosed on the basis of clinical signs compatible with HFMD (Sarma et al, 2009). A single study conducted to investigate an outbreak of HFMD in Calicut, Kerala, identified association of EV-71 by an immunological approach (Sasidharan et al, 2005). In the present study, use of sensitive molecular methods, RT-PCR and sequencing targeted against conserved and variable regions of the EV genome revealed the presence of significant EV RNA positivity as well as multiple types in the clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of two outbreaks of HFMD that occurred in the Kerala and West Bengal states of India in 2003 and 2007, respectively, have been reported (Sasidharan et al, 2005;Sarma et al, 2009). These investigations identified 119 cases of HFMD on the basis of clinical examination and serological tests.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemics of HFMD have been reported worldwide since the 1970s in Bulgaria, Hungary, UK, USA, Australia, and India with significant mortality and morbidity [3][4][5][6][7]. Large outbreaks due to enterovirus 71 have occurred from 1997 to 2000 in Malaysia, Taiwan, Singapore, and Japan [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[4] In India Sasidharan et al, reported HFMD epidemic caused by EV 71 from Calicut for the first time in 2003. [5] Later epidemics have been reported from Nagpur, [6] West Bengal [7] and Assam. [8] Infection is spread by direct contact with the virus.…”
Section: Discussionmentioning
confidence: 96%